INPH and parkinsonism: A positive shunt response with a negative tap test - Giannini, Giulia; Jusue-Torres, Ignacio; Mantovani, Paolo; Mazza, Liliana; Pirina, Alessandro; Valsecchi, Nicola; Milletti, David; Albini-Riccioli, Luca; Cevoli, Sabina; Yasar, Sevil; Palandri, Giorgio (Frontiers in Neurology, 2023)
Introduction The aim of this study was to compare clinical and functional performances of idiopathic normal pressure hydrocephalus (INPH) patients with and without parkinsonism at the initial evaluation, 72 h after the cerebrospinal fluid tap test (CSF TT), and 6 months after ventriculoperitoneal shunt (VPS) surgery. Materials and methods This is an observational prospective study on patients with INPH who underwent VPS. Patients were classified into INPH with parkinsonism (INPH-P+) and without parkinsonism (INPH-P−). We used the time up and go (TUG) test, Tinetti Performance-Oriented Mobility Assessment (POMA) test, INPH grading scale (INHPGS), and modified Rankin scale (mRS) at baseline, 72 h after CSF TT, and 6 months after VPS surgery. Results A total of 64 patients with probable INPH were included, 12 patients with INPH-P+ and 52 controls with INPH-P−. Patients with INPH showed significant improvement in all clinical and neurological parameters after VPS including TUG, Tinetti POMA, INPHGS, and mRS (p < 0.001) with the exception of mRS where there was no significant change 72 h after CSF TT compared to baseline for patients with INPH (p = 0.182). Patients with INPH-P+ performed significantly worse than patients with INPH-P− on Tinetti POMA and mRS at baseline, at 72 h post-CSF TT, and at 6 months post-VPS with INPHGS being worst at 72 h post-CSF TT. There was no difference between patients with INPH-P+ and patients with INPH-P− for TUG at baseline (p = 0.270), at 72 h post-CSF TT (p = 0.487), and at 6 months post-VPS (p = 0.182). Patients with INPH-P+ did not show any change in any of the parameters at 72 h post-CSF TT compared to baseline; however, there was a trend toward improvement on TUG (p = 0.058), Tinetti gait (p = 0.062), and Tinetti total (p = 0.067). INPH-P+ significantly improved in all parameters 6 months post-VPS compared to baseline except for mRS (p = 0.124). Patients with INPH-P− significantly improved in all parameters at 72 h post-CSF TT and at 6 months post-VPS compared to baseline, respectively, except on mRS 72 h after CSF TT (p = 0.299). Conclusion Patients with INPH and parkinsonism overall do worse than patients without parkinsonism. An unsatisfying response to the CSF tap test in INPH patients with parkinsonism should not be used as an exclusion criterion from VPS surgery since patients with and without parkinsonism showed significant improvement post-VPS.